The white dwarf binary pathways survey – VII. Evidence for a bi-modal distribution of post-mass transfer systems?. Issue 2 (11th March 2022) - Lagos, F; Schreiber, M R; Parsons, S G; Toloza, O; Gänsicke, B T; Hernandez, M S; Schmidtobreick, L; Belloni, D
ABSTRACT: Binary systems consisting of a white dwarf (WD) and a main-sequence companion with orbital periods up to ≈100 d are often thought to be formed through common envelope evolution which is still poorly understood. To provide new observational constraints on the physical processes involved in the formation of these objects, we are conducting a large-scale survey of close binaries consisting of a WD and an A- to K-type companion. Here, we present three systems with eccentric orbits and orbital periods between approximately 10 and 42 d discovered by our survey. Based on Hubble Space Telescope spectroscopy and high-angular resolution images obtained with the Spectro-Polarimetric High-contrast Exoplanet REsearch (SPHERE), we find that two of these systems are most likely triple systems while the remaining one could be either a binary or a hierarchical triple but none of them is a post-common envelope binary (PCEB). The discovery of these systems shows that our survey is capable to detect systems with orbital periods of the order of weeks, but all six PCEBs we have previously discovered have periods <2.5 d. We suggest that the fact that all of the systems we identify with periods of the order of weeks are not PCEBs indicates a transition between two different mechanisms responsible for the formation of very close (≲10 d) and somewhat wider WD + AFGK binaries: common envelope evolution and non-conservative stable mass transfer.